Mortality Salience, Self-esteem and Status Seeking - Caterina Giannetti; Raimondello Orsini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
According to the Terror Management Theory, the fear of death may induce anxiety and threaten individual self-esteem. To remove this fear, individuals need to obtain and sustain self-esteem, for example by competing in rank order tournaments, or by focusing on status seeking. Within an experimental setting, this paper investigates the effect of Mortality Salience on individual productivity, manipulating the information on subjects' relative performance in a real-effort task where the economic incentive is to not perform: in a first treatment subjects receive only private feedback, which may have effects on productivity via individual self-esteem, while in a second treatment subjects receive public feedback, which may have effects on productivity via status seeking. Our results suggest that the majority of subjects exposed to death-related thoughts tend to be more sensitive to in-group conformity when both types of feedback are provided.
Keywords: C91; C92; D12; 330